A 500‐Year Tree Ring‐Based Reconstruction of Extreme Cold‐Season Precipitation and Number of Atmospheric River Landfalls Across the Southwestern United States. Issue 11 (10th June 2018) - Steinschneider, Scott; Ho, Michelle; Williams, A. Park; Cook, Edward R.; Lall, Upmanu
Abstract: This study develops a reconstruction of the frequency of extreme cold‐season precipitation and the occurrence of landfalling atmospheric river (AR) storm tracks across the southwestern Unites States using a network of tree ring chronologies and the Living Blended Drought Atlas (LBDA), a 500‐year tree ring based reconstruction of the summer Palmer Drought Severity Index. The first two rotated empirical orthogonal functions of the LBDA across the Southwest are shown to relate well to previously identified patterns of regional AR activity. Accordingly, the rotated empirical orthogonal functions also record patterns of extreme precipitation associated with those ARs, albeit with some uncertainty introduced by nonextreme precipitation. A network of chronologies sensitive to cold‐season precipitation is then used to reconstruct the occurrence of landfalling ARs and extreme precipitation along the southern Californian coast, demonstrating for the first time the feasibility of reconstructing AR landfalls and extreme events in the Southwest based on spatial patterns in a network of dendroclimatic proxies. Plain Language Summary: Extreme precipitation and flood events are a significant hazard to society. Along the West Coast, many of these extreme events are linked to a particular type of storm called an atmospheric river. Intense atmospheric rivers that make landfall are rare, and this makes it difficult to assess the likelihood of these storms and whether this likelihood is changing over time. In this study, we present the first attempt to predict the occurrence of landfalling atmospheric rivers impacting the southwest coast of the Unites States over the past 500 years, as well as extreme precipitation associated with these storms. To do this, we use a series of tree ring chronologies that record winter precipitation amounts in the widths of tree rings, which for some trees can extend backward in time for hundreds of years. Because intense atmospheric rivers bring substantial precipitation amounts that extend far into the interior of the western Unites States, we show that a network of tree ring chronologies across this region can predict when atmospheric rivers made landfall along the coast. This enables a better understanding of past variability in these storms, which can be used to contextualize observed trends or predicted changes in storm frequency under anthropogenic climate change. Key Points: The first two EOFs of a reconstructed drought index in the southwestern Unites States relate to two major atmospheric river storm tracks over the region A network of tree ring chronologies in the Southwest can accurately reconstruct landfalling atmospheric rivers along the southwest coast The network of chronologies can also reconstruct the occurrence of extreme precipitation along the southern California coastline